2006
DOI: 10.1021/jf060254p
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Derivatives, Major Safflower (Carthamus tinctorius L.) Seed Antioxidants, Inhibit Low-Density Lipoprotein (LDL) Oxidation and Atherosclerosis in Apolipoprotein E-Deficient Mice

Abstract: The effects of defatted safflower seed extract and its phenolic constituents, serotonin derivatives, on atherosclerosis were studied. Ethanol-ethyl acetate extract of safflower seeds (SSE) inhibited low-density lipoprotein (LDL) oxidation induced in vitro by an azo-containing free-radical initiator V70 or copper ions. Two serotonin derivatives [N-(p-coumaroyl)serotonin, CS; N-feruloylserotonin, FS] and their glucosides were identified as the major phenolic constituents of the extract. The study with chemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 28 publications
2
93
0
2
Order By: Relevance
“…They suggested that the decreased plasma T-Chol level was due, in part, to the increased formation of HDL-Chol and the excretion of cholesterol. Koyama et al 17 also found in apolipoprotein E-deficient mice fed CS+FS and SSE for 15 weeks that serum T-Chol levels decreased significantly without a significant increase in the HDL-Chol level. These findings were inconsistent with our results in KHC rabbits.…”
Section: Effect Of Cs and Fs On Serum Lipid Levelsmentioning
confidence: 93%
See 4 more Smart Citations
“…They suggested that the decreased plasma T-Chol level was due, in part, to the increased formation of HDL-Chol and the excretion of cholesterol. Koyama et al 17 also found in apolipoprotein E-deficient mice fed CS+FS and SSE for 15 weeks that serum T-Chol levels decreased significantly without a significant increase in the HDL-Chol level. These findings were inconsistent with our results in KHC rabbits.…”
Section: Effect Of Cs and Fs On Serum Lipid Levelsmentioning
confidence: 93%
“…CS and FS were synthesized from 5-HTÁHCl, p-coumaric acid and trans-ferulic acid. 17 The purity of CS (96.4%) and FS (99.5%) was determined using HPLC.…”
Section: Preparation Of Safflower Seed Extractmentioning
confidence: 99%
See 3 more Smart Citations